2023
DOI: 10.1111/1756-185x.14840
|View full text |Cite
|
Sign up to set email alerts
|

Expression of calcitonin gene‐related peptide induces ligament degeneration through endochondral ossification in osteoarthritis

Abstract: AimOsteoarthritis (OA) is a disease in which degeneration occurs in various tissues such as cartilage and subchondral bone. Degeneration of ligaments also plays an important role in OA progression, resulting in an increase in chondrocytes and ossification, but the factor that causes this is still unclear. It is reported that the expression of calcitonin gene‐related peptide (CGRP) increases OA progression, and CGRP might play a role in ligament degeneration because CGRP has a function in endochondral ossificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Unfortunately, this knowledge is still unknown to many researchers. For example, in a recent study of the contribution of CGRP in OA mice stifles, the authors did not mention the sex of the animals used [76]. In addition, our process of validating the MI-RAT model confirmed that sterilized female rats favorably increased data homogeneity by reducing variability in pain outcome measures because estrogen supplementation interfered with central sensitization in OVX rats [27].…”
Section: Validity Of the Mi-rat Oa Model Coupled To A Calibrated Slig...mentioning
confidence: 87%
“…Unfortunately, this knowledge is still unknown to many researchers. For example, in a recent study of the contribution of CGRP in OA mice stifles, the authors did not mention the sex of the animals used [76]. In addition, our process of validating the MI-RAT model confirmed that sterilized female rats favorably increased data homogeneity by reducing variability in pain outcome measures because estrogen supplementation interfered with central sensitization in OVX rats [27].…”
Section: Validity Of the Mi-rat Oa Model Coupled To A Calibrated Slig...mentioning
confidence: 87%